The eagle and the hart : the tragedy of Richard II and Henry IV - Castor, Helen (Avid Reader Press, 2024)
"The dual biography of Richard II and Henry IV, two cousins whose lives played out in extraordinary parallel, until Henry deposed the tyrant Richard and declared himself King of England"--